Online children's development at nursery / Aminah Najihah Jaafar - Jaafar, Aminah Najihah (2014)
This research looked at Online Children's Development at Nursery. Currently, there is lack of communications between parents and nursery administrator and it is the main factor why parents are unable to monitor their children's progress at nursery. To overcome this problem, the researcher develops a website which is enabling the two way communication between both host and client which are the nursery administrator and parents. This project was developed using PHP which is stands for PHP Hypertext Pre-processor as the programming language. The researcher successfully develops a website that contained the progress at nursery for every children and at the same time it allowed more effective communication between nursery administrators as a host and parents as a client respectively. This project has been developed with many improvement were enhanced, especially in the communication part between both client and host.